Development of a Conflict Resolution Model Design based on Critical Reasoning in Elementary School Learning - Dianasari Dianasari; Bunyamin Maftuh; Ernawulan Syaodih; Sapriya Sapriya; Ma Arsenia C Gomez (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The conflict that occurred in Cirebon Regency is an example of the division between ethnic groups that have been taking place in Indonesia for more than a decade. The emotional toll of living in a conflict-ridden environment has led elementary school children to imitate conflict behavior in their school settings and in dealing with peers. To prevent the internalization and reproduction of conflict behavior, the role of educators is crucial thus the need for effective conflict resolution models- one of which is through the development of a critical reasoning-based conflict resolution learning model. This article aims to examine two main questions: (1) What educational theories underlie the development of a critical reasoning-based model? and (2) What is the preliminary design of a conflict resolution model in elementary school learning? This research adopts the Sukmadinata development model which simplifies the stages of Borg & Gall's educational R&D approach. The findings of this study reveal that: (1) three main educational theories form the foundation for developing conflict resolution models in Civics education—namely humanistic theory, progressivism, and reconstructionism; and (2) the initial design of the conflict resolution model encompasses five key elements: instructional syntax, social system, classroom management, support systems, and both instructional and nurturant effects. The contribution of this study lies in providing a theoretically grounded and practically applicable model of conflict resolution learning for elementary schools, which is oriented toward the cultivation of critical reasoning. This model not only serves as a pedagogical tool for teachers in areas vulnerable to social conflict, but also enriches Civics learning by integrating peace education and democratic values from an early age.